Influence of local leadership in poverty eradication in the state of Terengganu, Malaysia - Ahmad Aizuddin, Md Rami; Ramle, Abdullah; Abdullah, Ibrahim (2017)
Challenges in rural communities call for awareness of community leaders in overcoming these challenges. One of these challenges is the government's endeavour to ensure that the rural community development is parallel to the country's development, hence a credible. effective community leader is needed to achieve the country's development aspiration. This study was conducted in four rural communities in the state of Terengganu, Malaysia to identify the role played by local community leaders. These communities were selected based on their excellent achievement in community development programmes and contests. The objectives of this research are identifying the role of leaders in bringing success for every development programme and ascertaining the community leadership characteristics that can bring positively impact a community. The data for this study were obtained from observations and interviews with 40 informants who comprised of chairpersons and members of the villages development and safety committee (J3K) as well as local residents. The findings showed that effective community leadership plays a significant role as an agent of change and has the ability to positively impact to development of rural community. Besides that community leader's mane of effective leadership style is perceived to bring changes IIMOIV, the community in the social, economic and cultural aspects as well as changes in the way of thinking among rural communities. In this regard, leadership in these four communities is viewed to manifests die change into better leadership that can inspire other community leaders.